Reality-show – a gender analysis - Mateus, Samuel (2012)
In the second half of the 20th century a mutation occurred in television’s enunciative apparatus that the reality-show is one of the largest examples, in emphasizing not what is said but who says. Given the fluidity and the multiplicity of influences that reality-show presents itself there is a serious difficulty in putting it in a single genre. Trying to answer this problem, this paper puts the reality-show as an independent television genre with singular conventions that allow us to sketch a more precise genre definition. Pointing to the centrality of the everyday, to the scopophilic movement and to the emancipation of the spectator, we outline a definition that takes into account the specific and distinguishing "reality-show" television genre.